Conservation of Gene Order and Content in the Circular Chromosomes of ‘Candidatus Liberibacter asiaticus’ and Other Rhizobiales - Kuykendall, L. David; Shao, Jonathan Y.; Hartung, John S. (PLOS ONE, 2012)
‘Ca. Liberibacter asiaticus,’ an insect-vectored, obligate intracellular bacterium associated with citrus-greening disease, also called “HLB," is a member of the Rhizobiales along with nitrogen-fixing microsymbionts Sinorhizobium meliloti and Bradyrhizobium japonicum, plant pathogen Agrobacterium tumefaciens and facultative intracellular mammalian pathogen Bartonella henselae. Comparative analyses of their circular chromosomes identified 514 orthologous genes shared among all five species. Shared among all five species are 50 identical blocks of microsyntenous orthologous genes (MOGs), containing a total of 283 genes. While retaining highly conserved genomic blocks of microsynteny, divergent evolution, horizontal gene transfer and niche specialization have disrupted macrosynteny among the five circular chromosomes compared. Highly conserved microsyntenous gene clusters help define the Rhizobiales, an order previously defined by 16S RNA gene similarity and herein represented by the three families: Bartonellaceae, Bradyrhizobiaceae and Rhizobiaceae. Genes without orthologs in the other four species help define individual species. The circular chromosomes of each of the five Rhizobiales species examined had genes lacking orthologs in the other four species. For example, 63 proteins are encoded by genes of ‘Ca. Liberibacter asiaticus’ not shared with other members of the Rhizobiales. Of these 63 proteins, 17 have predicted functions related to DNA replication or RNA transcription, and some of these may have roles related to low genomic GC content. An additional 17 proteins have predicted functions relevant to cellular processes, particularly modifications of the cell surface. Seventeen unshared proteins have specific metabolic functions including a pathway to synthesize cholesterol encoded by a seven-gene operon. The remaining 12 proteins encoded by ‘Ca. Liberibacter asiaticus’ genes not shared with other Rhizobiales are of bacteriophage origin. ‘Ca. Liberibacter asiaticus’ shares 11 genes with only Sinorhizobium meliloti and 12 genes are shared with only Bartonella henselae.